Composing the Self and Reflecting the Others in Life Writing: Theories and Practices - Gautam, Mani Bhadra (Pursuits: A Journal of English Studies, 2022)
Life writing is an art of scripting and concretizing his/her own or others images and audio-visual things with ideas, views, feelings etc. into written form. It subjectivisms on composing the self and stimulates scholars to concretize their views, ideas and feelings in the practical ground of the real world reflecting the others’ lives from narratives of an imaginary world. Oral histories cannot be long lasting as it is said that the originality of the stories, events or incidents might be missing in shifting of time and so life writing theories help to bring the views into practice from the coaxers and coaches to the listeners. Life writers write about the self reflecting on the memory, experiences, identity and embodiment. Agencies play the roles from inner selves and outer impressions and question on the truth. Life writers seek the sites through coaxers, coaches, agencies and story tellers to expose the structuring modes of self-inquiry in different forms of ‘I’ as autobiographical, narrating and historical as addressee or the media in front of the consumers or audiences from one generation to the others. Academic debates in the Writing Departments are serious in its philosophical and theoretical terms and objective of this article is to find out the gaps and reduce the confusion about its tools and techniques. Thus, this article copes to the challenges of Life Writing.